Textiles in the neo-Assyrian empire: a study of terminology - Gaspa, Salvatore (Studies in ancient Near Eastern records, 2018)
The book analyses the Assyrian textile terminology of the first millennium BC. Terms for raw materials, textile procedures, and textile end products consumed in first-millennium BC Assyria are classified according to their meaning and compared with other dialects of Akkadian as well as other Semitic languages. The study also discusses the management of textile production and consumption in Assyria by the state administration